Hepatic Sinusoidal Obstruction Syndrome in a Patient With Multiple Myeloma Treated With CyBorD. Issue 7 (July 2019) - Tariq, Tooba; Dawdy, John; Goyal, Sachin; Mohamad, Bashar; Singh, Manmeet; Mutchnick, Milton; Ehrinpreis, Murray
Abstract : ABSTRACT: Hepatic sinusoidal obstruction syndrome (SOS) is a life-threatening state generally occurring as a complication of conditioning regimens used for hematopoietic stem cell transplant. Hepatic SOS after a standard dose of chemotherapy in malignancies is rare, and there are only a few cases in pediatric literature. We report a 56-year-old man with multiple myeloma who experienced SOS after being initiated on chemotherapy including cyclophosphamide, dexamethasone, and bortezomib and who experienced a delay in treatment with defibrotide, because it is currently approved by the Food and Drug Administration for only patients who develop SOS after hematopoietic stem cell transplant.